Effective and Versatile Synthesis of Ginkgotoxin and Its 4′-O-Derivatives through Regioselective 4′-O-Alkylation and 4′-O-Chlorination of 3,5′-O-Dibenzylpyridoxine - Huang, Boshi; Danso-Danquah, Richmond; Safo, Martin K.; Zhang, Yan (SynOpen, 2020)
A regioselective synthesis of ginkgotoxin and its derivatives is described. A blocking–deblocking strategy was employed in this new methodology, which relied on selective ketal protection of the 3- and 4′-hydroxy groups of pyridoxine. The key intermediate, O-dibenzylpyridoxine, was prepared in four steps with a reasonable yield. The present synthetic route enables convenient and versatile preparation of diversified 4′-substituted pyridoxine derivatives.
Keywords: ginkgotoxin; pyridoxine